Intermediate hamiltonian hilbert space coupled cluster method: theory and pilot application - Eliav, Ephraim; Borschevsky, Anastasia; Shamasundar, K. R.; Pal, Sourav; Kaldor, Uzi (International Journal of Quantum Chemistry, 2009)
The intermediate Hamiltonian state universal (Hilbert-space) coupled-cluster method is presented, using a formalism similar to that developed for the valence universal (Fock-space) approach. The method is expected to be applicable to many states not accessible by traditional multiroot multireference all-order size-extensive approaches. A pilot application to excited states of atomic beryllium shows good convergence and agreement with experiment and full CI values. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 109: 2909-2915, 2009
Keywords: coupled cluster; Hilbert space; intermediate Hamiltonian